The benefit of hearing aids in adults with hearing loss during the Covid–19 pandemic - Çıldır, Bünyamin; Tokgoz-Yılmaz, Suna (Journal of Surgery and Medicine, 2022)
Background/Aim: Hearing aids, cochlear implants, and guidance are highly effective in improving communication skills and the quality of life of individuals with hearing loss. During the Covid-19 pandemic, patients with hearing loss, especially those living far from city centers, faced insufficient device use due to their inability to go to the hospitals and device centers. This study aimed to evaluate the effects of remote monitorization of sound amplification in adults using cochlear implants and/or hearing aids during the lockdown period. Methods: In this cross-sectional study, we recruited 98 individuals with post-lingual cochlear implants (n=38) and hearing aids (n=60). Patients on hearing aids followed before the Covid-19 pandemic were guided with a remote computer connection during the pandemic. All participants filled out the Spatial Hearing Questionnaire (SHQ), the short version of Speech Spatial Quality of Questionnaire (SSQ12), Short Form-36 quality of life questionnaires (SF-36), Satisfaction with Amplification in Daily Life Questionnaire (SADL), and the Coronavirus 19 Phobia Scale (C19P-S) via google questionnaire. Results: During the lockdown period, there were significant increases in the spatial perception scores (SSQ12) of cochlear implant and hearing aid users (P<0.05). A moderate correlation was found between SSQ12 and SHQ scores in cochlear implant (r=0.482, P=0.021) and hearing aid users (r=0.512, P=0.011). During the lockdown period, the SADL overall scores were significantly higher among cochlear implant users (P<0.05). When the subscales of SF-36 for both cochlear implant and hearing aid users were compared with the normative values of these subtests (energy/vitality, role limitations due to physical dysfunctions and emotional problems, mental health, and pain), it was observed that there was a significant improvement in the scores of individuals using hearing aids and cochlear implants (P<0.05). Conclusion: During the lockdown period, hearing performance, quality of life, and hearing aid satisfaction of patients using cochlear implants and hearing aids increased after tele-audiology guidance.